Evaluation of the trophic benthic diatom index in some main rivers of Thailand - Pongpan Leelahakriengkrai (2018)
The evaluation of the trophic benthic diatom index in 6 rivers of Thailand. Samples were collected from 6 regions in Thailand: Ping River (northern regions), Tha Chin River (central regions), Chi River (northeast regions), Chanthaburi River (eastern regions), Kwai River (western regions) and Tapee River (southern regions). Samples were taken from the upper, middle and lower parts during March 2008, August 2008 and January 2009. A total of 214 species of benthic diatoms were found and 104 species of benthic diatoms with high relative abundance ( > 1%) in each site were selected to establish the Thailand Diatoms Index. The estimation of indicator values were classified into seven classes that were based on a weighted averages approach (WAs) and these were calculated based on the major environmental factors of BOD5, nitrate nitrogen ammonia nitrogen and SRP with an abundance of benthic diatoms from each site. In this investigation, the ranges of indicator values were 2.3-4.8. The comparison of indicator values of the Thailand Diatoms Index with other Thailand indexes showed no more difference in indicator value but showed a high difference of indicator value when compared with other the indexes of other foreign countries thus, the Thailand Diatoms Index is considered appropriate to indicate the trophic status for rivers of Thailand. © 2014 AENSI Publisher All rights reserved.